Peran Penting Manajemen Persuratan Dalam Menunjang Kinerja Organisasi - Darmansah, Tengku; Siregar, Nur Khofifah; Marpaung, Wardatun Thaibah; M, Marsyeli; M, Marsyela (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Mail management includes managing incoming and outgoing mail, archiving, as well as monitoring and controlling documents to increase the efficiency and effectiveness of organizational operations. The research uses qualitative methods with a literature study approach. This research finds that effective correspondence management can speed up the internal and external communication process, reduce the risk of losing important documents, and increase information accessibility. In addition, the application of technology in correspondence management has been proven to contribute significantly to improving organizational performance. This research emphasizes the importance of integrating effective correspondence management as part of an organization's management strategy to achieve optimal performance.